The Middle East: the cradle of civilization, by Galina M. Yemelianova. Edinburgh: Edinburgh University Press, 2019. Pp. 218. ISBN: 9781474416337 - Akhmetova, Elmira (The Islamic Foundation, 2020)
This piece a review of the book on Muslims of Central Asia